Quantum dynamics study of the Langmuir-Hinshelwood H+H recombination mechanism and H-2 formation on a graphene model surface - Kerkeni, B; Clary, D (2007)
We examine in this paper the associative desorption of two hydrogen atoms on a slab model that mimics a C(0 0 0 1) surface. Initially the two separated H atoms are physisorbed onto the graphene surface, then diffuse and recombine and H2 gets desorbed into the gas phase. We use density functional theory (DFT) on a supercell model and apply periodic boundaries to build a potential energy surface (PES). The reaction is barrier less and exhibits a small H2 vdW well on the global potential energy surface. We employ a two-dimensional quantum dynamics method exploiting the hyperspherical coordinates and report reaction probabilities for this mechanism. The calculations are performed for collision energies ranging from 1 to 15 meV relevant to the interstellar medium (ISM). The entrance channel dominates the reaction and the vibrational excitation of the desorbed H2 is important and peaked at v′ = 8. © 2007 Elsevier B.V. All rights reserved.